INTEGRATION OF LOCAL VALUES IN HISTORY LEARNING AT SMA NEGERI 5 MEDAN - Hidayat, Muhammad Abdi; Nasution, Abd. Haris; Nasution, Soviannur (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This research is titled